Perbandingan Tingkat Literasi Fisik Siswa Sekolah Dasar di Daerah Perkotaan dan Pedesaan - Nadia Amelia Putri; Lukmannul Haqim Lubay; Wulandari Putri; Achmad Syakur Fahri (Universitas Hamzanwadi, 2026)
Physical literacy is a key construct in physical education, encompassing movement competence, motivation, confidence, knowledge, and sustained engagement in physical activity. The living environment may influence children’s physical literacy development, particularly across urban and rural contexts. This study examined differences in the physical literacy levels of elementary school students in urban and rural areas of Bandung Regency, Indonesia. A quantitative comparative design was employed involving 591 students from Soreang District (urban) and Cangkuang District (rural). Data were collected using the Physical Literacy in Children Questionnaire (PL-C Quest) and analyzed through descriptive statistics, normality and homogeneity tests, and the Mann–Whitney test. The findings revealed a significant difference in physical literacy between students from urban and rural areas (p = 0.001), with urban students demonstrating higher mean scores. These results suggest that living environment may be associated with children’s physical literacy development, potentially through disparities in access to facilities, physical activity experiences, and supportive learning environments. The study underscores the need to promote equitable physical activity opportunities and strengthen physical education provision across regions.